Perspectives on rehabilitation of children with cerebral palsy: exploring a cross-cultural view of parents from India and Canada using the international classification of functioning, disability and health. Issue 23 (6th November 2018) - Jindal, Pranay; MacDermid, Joy C.; Rosenbaum, Peter; DiRezze, Briano; Narayan, Amitesh
Abstract: Purpose: To explore parents' perspectives on rehabilitation of their child with cerebral palsy and their information needs. Methods: Semistructured interviews were conducted with parents of children with CP from India ( n = 11) and Canada ( n = 7). Data were analyzed through an interpretive description approach using the International Classification of Functioning, Disability and Health framework. Results: Body Structure and Function: Indian parents were more focused on fixing body structure and function challenges, and independent walking, than Canadian parents. Activity and Participation: All Canadian children were actively involved in school and fun activities in the community. Due to lack of accessible services, Indian children had less school and community participation. Environmental factors: accessible communities, occupational therapy services and greater use of assistive devices enabled Canadian children. Social and cultural beliefs, lack of access to services and inaccessible communities were the barriers experienced by Indian parents. Information needs : both groups needed information to make their child more functional. Conclusion: Canadian parents experience a more enabling environment and express a more social view of their child's health, suggesting both education on the International Classification of Functioning, Disability and Health principles and services are needed to better enable and empower Indian parents. There remains a need for healthcare professionals and services in both countries to be more family-centered. Implications for rehabilitation: To help parents in rehabilitating their children with cerebral palsy (CP), in India, there is a need to (1) incorporate ICF education into medical curricula and clinical practice; (2) increase the availability of skilled healthcare professionals and centers; (3) make infrastructural and policy reforms to make the society more accessible for the disabled children. Education, counseling and awareness about CP might help both groups of parents, society, and HCPs to change their beliefs and attitudes regarding CP and its rehabilitation. Both countries would benefit from user-friendly and transparent policies. This will help parents to become more aware of them and use them in the rehabilitation process.